Experimental Study of Effects of the Third Medium on the Maximum Friction Coefficient between Wheel and Rail for High-Speed Trains - He Ma; Yan Niu; Xiaochun Zou; Jun Zhang (Shock and Vibration, 2021)
The changes of the friction coefficient between wheel and rail affect the wheel-rail adhesion characteristics of high-speed trains. The adhesion state in the wheel-rail contact area could be distinguished by the maximum friction coefficient between wheel and rail. The wheel-rail adhesion is of great significance for high-speed train traction. In order to study the influence of water, oil, fallen leaves, quartz sand, or their mixtures on the maximum friction coefficient between high-speed wheel and rail, a wheel-rail contact test bed is built to carry out the wheel-rail contact test and wheel-rail friction contact test. The comparative analysis of the test results shows that the axle load has little influence on the maximum friction coefficient between wheel and rail. Water, oil, and fallen leaves would reduce the maximum friction coefficient. Quartz sand could increase the maximum friction coefficient in a short time, while the excessive static friction coefficient would damage the wheel and rail. Besides, the maximum friction coefficient of water, oil, and fallen leaves mixing in pairs is lower than each of them existing alone. Both water and oil could increase the adhesion of quartz sand, and the effect of water is better. Therefore, when the sand still could not meet enough traction, it could be considered to add some water to increase the wheel-rail adhesion.